Backtesting of trading strategy and application of this strategy on Germany´s stock index DAX30 - Kuchár, Peter (2019)
The main objective of this thesis is to create successful intraday trading strategy by using technical analyses and proper risk management. Thesis will be divided into two parts where first part will consist of theoretical knowledge necessary to understand aspects of the trading and market analyses. Second part will be application of this knowledge in order to create successful trading strategy.Thesis shows steps necessary for creating successful trading strategy and how to approach historical testing of profitability of trading strategy. As underlying instrument DAX30 was chosen and for the testing period years of various market conditions were picked. Last chapter of thesis sums up performance of trading strategy in recent market and is represented by selected metrics of profitability.The main contribution of the bachelor thesis is my very own approach to market analyses, creation of profitable trading strategy and conclusion and interpretation of obtained results.